2006
DOI: 10.1074/jbc.m603609200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 Replication by Amphotericin B Methyl Ester

Abstract: Membrane cholesterol plays an important role in human immunodeficiency virus type 1 (HIV-1) particle production and infectivity. Here, we have investigated the target and mechanism of action of a cholesterol-binding compound, the polyene antifungal antibiotic amphotericin B methyl ester (AME). We found that AME potently inhibited the replication of a highly divergent panel of HIV-1 isolates in various T-cell lines and primary cells irrespective of clade or target cell tropism. The defects in HIV-1 replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 72 publications
5
80
0
Order By: Relevance
“…This is supported by the observation that nystatin affected properties of the arginine and glucose transporters in yeast plasma membrane vesicles (20). Further, the amphotericin B methyl ester inhibited the replication, assembly, and release of HIV-1 by interfering with the ion channel viral protein U (VPU) (18,21). Microarray studies with S. cerevisiae clearly show an increase of expression of transport proteins on treatment with the polyenes amphotericin B and nystatin (22,23).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This is supported by the observation that nystatin affected properties of the arginine and glucose transporters in yeast plasma membrane vesicles (20). Further, the amphotericin B methyl ester inhibited the replication, assembly, and release of HIV-1 by interfering with the ion channel viral protein U (VPU) (18,21). Microarray studies with S. cerevisiae clearly show an increase of expression of transport proteins on treatment with the polyenes amphotericin B and nystatin (22,23).…”
Section: Discussionsupporting
confidence: 56%
“…Answering the question of how natamycin changes the membrane properties starts with the premise that the antibiotic action is attributable to binding to ergosterol (7), thereby affecting the functional properties the sterol has on membrane proteins either via ergosterol-rich domains (17) or more directly by interfering with a direct ergosterol-protein interaction. The different oxygen functions of natamycin may play a role in the latter mechanism, as is also suggested for other polyenes (6,18). A disruption of the equilibrium of free sterols to sphingolipids by natamycin may also be responsible for the inhibition of ergosterol-dependent protein functions because sterols and sphingolipids work together to carry out a wide variety of functions (19).…”
Section: Discussionmentioning
confidence: 93%
“…SIV Env and HIV Env have remarkably long cytoplasmic domains. It has been recently reported that the second-site reversion mutants of SIV and HIV-1 that were resistant to amphotericin B methyl ester (AME), a cholesterol-binding compound, had truncated Env cytoplasmic domains (36). It was suggested that the truncated protein had a higher potential for movement in the lipid bilayer, which resulted in the escape from inhibition by AME.…”
Section: Msd Core Mutant Viruses Show Defects In Infectivitymentioning
confidence: 99%
“…It is intriguing that TIP47 possesses a hydrophobic cleft of dimensions comparable to those of the hydrophobic CsA-binding site on CypA (19). Additionally, gp41 cytoplasmic tail truncations rescue HIV-1 replication from the antiviral compound amphotericin B methyl ester (34). Taken together, these observations prompted us to determine if gp41 cytoplasmic tail mutants would rescue HIV-1 from the CsAinduced defects in Env incorporation.…”
mentioning
confidence: 99%